1990
DOI: 10.1210/endo-126-5-2296
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Significant Effect of Neuropeptide Y to Suppress Growth Hormone Release by Stimulating Somatostatin Discharge*

Abstract: Neuropeptide Y (NPY) is a peptide found in a variety of hypothalamic loci which is frequently colocalized with catecholamines. It is also secreted into hypophyseal portal vessels. The injection of NPY into the third ventricle (3V) lowered plasma GH levels in conscious, freely moving male rats. To determine the physiological significance of the hypothalamic inhibitory action of the peptide, highly specific antiserum directed against NPY was injected into the 3V of conscious rats. 3V injection of the antiserum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 8 publications
0
67
1
1
Order By: Relevance
“…This has been shown by double-labeling experiments for GHS-R and NPY (Willesen et al 1999, Tannenbaum et al 2003, as well as by c-fos expression upon GHS activation in combination with NPY mRNA expression (Dickson & Luckman 1997). Rettori et al (1990) reported that the link between NPY and the suppression of GH in the circulation is mediated by a discharge of SRIF. Injections of NPY led to a suppression of GH lasting, after a delay of about 30-60 min, up to 2 h. They further established a direct link between NPY axons and SRIF neurons by receptor analysis.…”
Section: Ghrelin-npy Pathwaymentioning
confidence: 85%
See 1 more Smart Citation
“…This has been shown by double-labeling experiments for GHS-R and NPY (Willesen et al 1999, Tannenbaum et al 2003, as well as by c-fos expression upon GHS activation in combination with NPY mRNA expression (Dickson & Luckman 1997). Rettori et al (1990) reported that the link between NPY and the suppression of GH in the circulation is mediated by a discharge of SRIF. Injections of NPY led to a suppression of GH lasting, after a delay of about 30-60 min, up to 2 h. They further established a direct link between NPY axons and SRIF neurons by receptor analysis.…”
Section: Ghrelin-npy Pathwaymentioning
confidence: 85%
“…Thus, compared with a previously suggested model (Farhy & Veldhuis 2005), the major novel features of the present model are a) the role played by NPY, a powerful orexigenic hormone, which also stimulates the release of SRIF (Rettori et al 1990), and b) the dissimilar functions of ghrelin in the hypothalamus and in the pituitary. Furthermore, the predictions of this model were experimentally tested and confirmed in the present report.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, NPY may suppress the somatotrophic axis via stimulation of hypothalamic somatostatin release. 44,45 Hence, the observed reduction in PeVN somatostatin mRNA expression in obese A y /a mice may be secondary to reduced Arc NPY mRNA expression. Since NPY inhibits the growth axis, 20,21 a reduction in Arc NPY would increase circulating GH and hence IGFI levels.…”
Section: Discussionmentioning
confidence: 98%
“…This hypothesis is supported by previous data showing that leptin receptors are present in NPY neurones located in the arcuate nucleus of the hypothalamus, as well as immunohistochemical data showing synaptic connections between NPY-connecting neurones and periventricular neurones of the hypothalamus. 16 Further studies looking at the effects of leptin on GH secretion in NPY knock-out mice should help to clarify this possibility. Since we have previously found that leptin inhibits in vitro somatostatin secretion and somatostatin mRNA levels by rat fetal neurones in monolayer culture, 17 it was possible that the stimulatory effect of leptin on GH secretion could be mediated by regulating hypothalamic somatostatin andaor GHRH tone.…”
Section: Leptin and Gh Secretionmentioning
confidence: 99%